Heat reliability analysis of thermoelectric generators (TEG) based on heat transfer process. Issue 2 (January 2021) - Li, Xinchun; Cui, Lijie; Zhang, Liang; Wang, Zhongwei
Abstract: Thermoelectric generator (TEG) for output power is generated in different temperature. Its heat reliability is effect on the life length. In this paper a one- dimensional transient heat- transfer model of thermoelectric generator has been proposed and the temperature field of TEG has been given. The reliability model of TEG has been established for analyzing the TEG's life by considering the TEG structure compositions. The TEG life length has been studied under different heat flux per unit time conditions according to reliability distribution function. The results show the output power of TEG is increased when the temperature of TEG structure is increasing. But, the TEG life length is reduced with increasing temperature. Therefore, the TEG temperature is large effect on the life length of TEG.